What are the conclusions of the recent studies about administrating vitamin C in sepsis? The review - Wróblewski, Wiktor; Zając, Marlena; Gruca, Dariusz; Borowiecka, Monika; Buksak, Dagmara (Quality in Sport, 2023)
Introduction and purpose: Sepsis is defined by the Sepsis-3 definition as life-threatening organ dysfunction caused by a dysregulated host response to infection1. Common manifestations of sepsis are fever, tachycardia, tachypnoea, confusion, hemodynamic dysfunction, and worsening of tissue perfusion. Sepsis may cause septic shock. The immune system produces reactive oxygen species which can also have an adverse influence on vasoconstruction5. There is a decrease in vitamin C levels in the plasma of patients with multiple organ failure6. Vitamin C plays a role in the synthesis of catecholamines and has antioxidant properties. The usage of vitamin C in sepsis patients has been arousing expectations for many years. Brief description of the state of knowledge: The current state of knowledge indicates that there is no beneficent effect of ascorbic acid on the population which suffered from sepsis. What is more, there is some proof that administrating that vitamin can be noxious and factor into brain functions19. There are also suggestions that it could increase mortality8. Conclusions: Recent studies do not recommend ascorbic acid as a treatment for sepsis. There is not out of the question that in some subpopulations due to pathogens or failed organs administrating vitamin C would benefit. Further research on this topic needs to be followed up.